Migration and the Foreign in Contemporary Spanish Poetry: El sueño de Dakhla (Poemas de Umar Abass) by Manuel Moya - Debra Faszer-McMahon (Studies in 20th & 21st Century Literature, 2012)
Many critical studies have addressed the issue of immigration in contemporary Spanish narrative and film, but far fewer have analyzed this topic within the context of poetry. The representation of immigrant experience in poetic texts is significant not only because poetic works have received less attention, but also because of the significance of poetry within North African and Islamic culture. Manuel Moya’s recent award-winning collection places the question of North African immigration as a central concern. The text purports to offer a compilation of poetry produced by the Western Saharan immigrant Umar Abass, who currently resides in Madrid. The work focuses on the experience of exile, and employs the poetic yo to describe exilic longing and explore the bonds of friendship. What the text does not mention, however, is that Abass, far from being a Saharan immigrant, is in fact a pseudonym employed by Moya. The poetic yo thereby elides the silence of the immigrant community through a veiled pseudonymic existence. This study analyzes what such identification between the poetic yo and the immigrant other signifies in the context of changing migration patterns and cultural frameworks in contemporary Spain.
Keywords: immigration; poetry; Manuel Moya; North Africa; Western Sahara; exile; poetic yo; friendship; other; identity